Emergency Department Visits for Gastroenteritis Before and After Rotavirus Vaccine Implementation in 2006. Issue 10 (October 2015) - Calello, Diane P.; Allegra, Stephen J.; Cochrane, Dennis G.; Eskin, Barnet; Allegra, John R.
Abstract : Objectives: Gastroenteritis (GE) accounts for a significant number of emergency department (ED) visits in children. Several studies since the introduction of a new rotavirus vaccine in 2006 have found decreases in rotavirus illness. We sought to determine in a large multicenter ED database whether there was also a decrease in ED visits in young children for GE. Methods: Design : Retrospective cohort of ED visits. Setting: 28 EDs with annual visits between 22, 000 and 82, 000. Population: Consecutive patients between January 1, 1996, and December 31, 2011. Protocol: We identified GE visits using International Classification of Diseases 9th revision (ICD-9) codes. For each year, less than 5 years, we determined the average daily percent of total ED visits for GE. We calculated the decreases from 2005 to 2011 in the average daily percent GE visits for each year of life and their 95% confidence intervals. Results: There were 7, 740, 823 total visits in the database, and 811, 317 (10.5%) are younger than 5 years. The annual percent of GE visits rose for all years of life from 1999 to 2005 and then decreased from 2005 to 2011. The decreases from 2005 to 2011 were greatest in the earliest years of life ranging from 41% in the first year of life to 15% in the fifth year of life. Conclusions: We found a decrease in average daily ED visits for GE in each year of life for those younger than 5 years after the introduction of the rotavirus vaccine. This was most pronounced during the earliest years of life.